2013
DOI: 10.1016/j.cllc.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Southwestern Oncology Group Phase II Trial (S0526) of Pemetrexed in Bronchioloalveolar Carcinoma Subtypes of Advanced Adenocarcinoma

Abstract: Bronchioloalveolar carcinoma (BAC) subtypes of lung adenocarcinoma represent approximately 10% to 15% of new non-small-cell lung cancer cases (NSCLC). Based on preclinical data supporting the relevance of alpha-folate receptors in BAC, this trial was designed to assess pemetrexed in patients with this pathologic subtype of lung adenocarcinoma. This trial demonstrated that single-agent pemetrexed is active against this histologic subset. Background Pemetrexed, a multitargeted antifolate drug, is an active agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Our DCR and PFS results were similar to those previously reported in an advanced BAC population [4,5,[7][8][9][10][11]. DCR did not differ between therapeutic arms or pathological subtypes, although there was a strong interaction between treatment effect (arm E versus CP) on PFS and mucinous and NM subtypes (p=0.009) (figure 3), as previous studies have suggested [10].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our DCR and PFS results were similar to those previously reported in an advanced BAC population [4,5,[7][8][9][10][11]. DCR did not differ between therapeutic arms or pathological subtypes, although there was a strong interaction between treatment effect (arm E versus CP) on PFS and mucinous and NM subtypes (p=0.009) (figure 3), as previous studies have suggested [10].…”
Section: Discussionsupporting
confidence: 79%
“…Our study population was similar to that of previous trials assessing advanced BAC, especially in terms of the relative proportion of NM (51%) and mucinous (42%) tumours [5,7,8,9,10,11]. In line with previous reports, EGFR and KRAS mutations were detected in 5.6% (6-22%) [9,10,11] and 27% (10-30%) [2,3] of cases, respectively.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Response rates to chemotherapy have been reported between 21% to 32% (18), and were either lower than or equal to the rates in patients with all types of adenocarcinoma. Pemetrexed has been reported to be active and well tolerated in patients with adenocarcinoma BAC subtypes (19). In this case, the patient did not get response to chemotherapies (including pemetrexed).…”
Section: B a C D E Fmentioning
confidence: 78%
“…Several chemotherapy trials have shown median survival of about 1 year (11,12). Targeted drug trials have reported only minimal improvement so far (13)(14)(15)(16)(17)(18). Lung transplantation for BAC was not considered as a therapeutic option in the 2007 report on evidence-based clinical practice guidelines published by the American College of Chest Physicians (19).…”
Section: Primary Lung Cancermentioning
confidence: 99%